STUDIES OF COATINGS FROM FIGURED OF THE ELEMENTS OF PAVING (FEP) WITH CORRUGATED BASE FROM TOOTHED ELEMENTS OF PYRAMIDAL SHAPE ON THE HORIZONTAL AND INCLINED SURFACES (Academic journal Industrial Machine Building Civil Engineering, 2017)
The new constructive-technological solutions of coatings from FEP (figured of the elements of paving) with the modified geometric by shape of the base were developed. Base FEP consisted of one, five or nine toothed of the elements of pyramidal shape was corrugated. The plan of the experiment and conducted laboratory studies on the effect geometric form of the base of a single FEP on the qualitative characteristics of coatings, located on the horizontal and inclined surfaces under the influence of a longitudinally applied load, was compiled. The experiment results analysis showed that the coatings from FEP with five and nine of the toothed elements in the base prevents the shift more effectively than the traditional coatings.
Keywords: figured element of paving – FEP; coatings; a pyramidal shape; a longitudinal shift